The potential effects of isoflavones on nuclear receptor modulation in bone remodeling: A review - Haryati Ahmad Hairi, Nor Hidayah Mustafa, Putri Ayu Jayusman, Ahmad Nazrun Shuid (Journal of Applied Pharmaceutical Science, 2023)
Isoflavones are plant-based compounds that act as phytoestrogens by mimicking the action of estrogen. Osteoblasts and osteoclasts are the key cells for bone remodeling, a process that includes bone proliferation, differentiation, deposition, and resorption. Studies have demonstrated that isoflavones, a class of flavonoids found almost exclusively in soybeans, could prevent bone loss. Recent findings revealed that isoflavones could activate nuclear receptors (NRs) and regulate bone formation and resorption processes. This current research discussed the principal actions of isoflavones mediated by NRs on bone remodeling such as steroid receptors (estrogen receptor, estrogen-related receptor, and androgen receptor) and metabolic receptors including peroxisome proliferator-activated receptor-γ. Isoflavones modulate osteogenesis by fine-tuning physiological responses on NR sensors and their transcriptional networks. Hence, this present review will dive deep into the use of several isoflavones as potential osteoporosis treatment through NR-controlling gene regulation.
Keywords: Isoflavones, nuclear receptor, bone remodeling, bone formation, bone resorption